Hepcidin resistance in dysmetabolic iron overload - Rametta, Raffaela; Dongiovanni, Paola; Pelusi, Serena; Francione, Paolo; Iuculano, Federica; Borroni, Vittorio; Fatta, Erika; Castagna, Annalisa; Girelli, Domenico; Fargion, Silvia; Valenti, Luca (Liver international, 2016)
Background & Aims Dysmetabolic iron overload syndrome (DIOS) is a frequent condition predisposing to metabolic, cardiovascular and hepatic damage, whose pathogenesis remains poorly defined. Aim of this study was to characterize iron metabolism in DIOS. Methods We evaluated 18 patients with DIOS, compared to 18 with nonalcoholic fatty liver and 23 healthy individuals with normal iron status, and 10 patients with hereditary haemochromatosis by a 24‐h oral iron tolerance test with hepcidin measurement and iron metabolism modelling under normal iron stores. Results Dysmetabolic iron overload syndrome patients had higher peak transferrin saturation and area under the‐curve of transferrin saturation than subjects with normal iron status, but lower values than haemochromatosis patients (P < 0.05 for all). Conversely, they had higher peak circulating hepcidin levels and area under the curve of hepcidin than the other groups (P < 0.05 for all). This was independent age, sex, haemoglobin, ferritin, and transferrin saturation levels (P = 0.0002). Hepcidin increase in response to the rise in transferrin saturation (hepcidin release index) was not impaired in DIOS patients. Viceversa, the ability of the hepcidin spike to control the rise in transferrin saturation at the beginning of the test (hepcidin resistance index) was impaired in DIOS (P = 0.0002). In DIOS patients, the hepcidin resistance index was correlated with ferritin levels at diagnosis (P = 0.016). Conclusions Dysmetabolic iron overload syndrome is associated with a subtle impairment in the ability of the iron hormone hepcidin to restrain iron absorption following an iron challenge, suggesting a hepcidin resistance state. Further studies are required to better characterize the molecular mechanism underpinning this new iron metabolism alteration.